Catheter treatment of junctional reciprocating tachycardia - Almiz, P. A.; Stychynsky, A. S.; Plyska, N. V.; Pokanevitch, A. V.; Kovalchuk, A. V.; Tkachuk, S. L. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The analysis of basic electrophysiologic features of junctional reciprocating tachycardia and results of catheter ablation for this arrhythmia were held in this work.